1989
DOI: 10.20870/oeno-one.1989.23.1.1726
|View full text |Cite
|
Sign up to set email alerts
|

Mise en évidence de polyamines (putrescine, cadaverine, nor-spermidine, spermidine et spermine) dans les feuilles et les grappes de <em>Vitis vinifera</em> L.

Abstract: <p style="text-align: justify;">Cinq polyamines libres, la putrescine, la cadavérine, la nor-spermidine, la spermidine et la spermine, ont été mises en évidence dans les feuilles et les grappes du Cabernet- Sauvignon et de l'Ugni blanc. La spermidine est toujours la polyamine la plus abondante. La cadavérine est faiblement représentée ou absente selon le cépage ou l'organe considéré.</p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Ethanolamine and ethylamine were found in grapes by Ough, Daudt, and Crowell (1981); ethylamine, ethanolamine and putrescine were found in grapes by Del Prete et al (2009) and Broquedis et al (1989) also found putrescine. Histamine was absent in SM musts, but small quantities of this amine were found in Spanish grapes by Vidal-Carou et al (1990).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Ethanolamine and ethylamine were found in grapes by Ough, Daudt, and Crowell (1981); ethylamine, ethanolamine and putrescine were found in grapes by Del Prete et al (2009) and Broquedis et al (1989) also found putrescine. Histamine was absent in SM musts, but small quantities of this amine were found in Spanish grapes by Vidal-Carou et al (1990).…”
Section: Discussionmentioning
confidence: 92%
“…Some authors have reported the presence of some biogenic amines in grapes. Broquedis, Dumery, and Boucard (1989) reported the presence of polyamines, particularly putrescine and spermidine, whereas Vidal-Carou, Ambatlle-Espunyes, Ulla-Ulla, and Mariné-Font (1990) found small quantities of histamine. Del Prete, Costantini, Cecchini, Morassut, and Garcia-Moruno (2009) in musts from seven different cultivars found only ethanolamine, ethylamine and putrescine.…”
Section: Introductionmentioning
confidence: 99%
“…Spermidine and putrescine have been detected in grapes. According to Broquedis et al (1989), these amines are found in the pericarp of Cabernet Sauvignon berries. However, putrescine can also be produced by lactic acid bacteria (Lactobacillus hilgardii and Lactococcus plantarum) from the degradation of the amino acid arginine or the amino acid derived ornithine (Arena and Manca de Nadra, 2001).…”
Section: Types Of Bioactive Amines In the Winesmentioning
confidence: 99%
“…Biogenic amines can also be present in the must itself (Daeschel, 1996). Putrescine in grapevines has been associated with the potassium deficiencies of the soil (Brodequis, Dumery, & Bouard, 1989). It is possible for this amine to accumulate in the grapes, and, as a result, remain in the wine.…”
Section: Introductionmentioning
confidence: 99%